Urethral Catheterization Is Not Necessary During Nononcological Laparoscopic Pelvic Surgery. Issue 4 (December 2019) - Nevins, Edward J.; Nevins, Elizabeth G.; Moori, Parisa L.; Strong, Catherine; Al-Zubaidi, Samim; Wayman, John; Karat, Dayalan
Abstract : Objectives: Expert opinion remains divided regarding whether routine urethral catheterization is required before nononcological laparoscopic pelvic surgery. Catheterization is thought to reduce the incidence of bladder injury when inserting a suprapubic laparoscopic port and prevent obstruction of the view of the pelvis because of bladder filling. However, catheterization comes with a risk of nosocomial infection and harbors financial cost. Moreover, indwelling catheters inhibit early mobilization and increase postoperative discomfort. Methods: A systematic review was undertaken using the Meta-Analysis of Observational Studies guidelines to identify eligible publications. End points included bladder injury, positive postoperative urinary microbiology, and postoperative urinary symptoms. Results: The reported incidence rates of laparoscopic bladder injury in included publications ranges from 0% to 1.3%. Importantly, bladder injury has occurred during both catheterized and noncatheterized operations. Our meta-analysis also shows that patients who are catheterized have a 2.33 times relative risk of developing postoperative positive microbiology in their urine ( P = 0.01) and a 2.41 times relative risk of postoperative urinary symptoms ( P = 0.005), when compared with noncatheterized patients. Conclusions: This meta-analysis indicates that omitting a catheter in emergency and elective nononcological laparoscopic pelvic surgery may be a safe option. Catheterization does not remove the risk of bladder injury but results in more urinary tract infections and symptoms. It may be reasonable to ask a patient to void immediately before anesthesia, after which an on-table bladder scan should be performed. If there is minimal residual volume, a urinary catheter may not be necessary, unless operative time is estimated to be greater than 90 minutes.